High-dose vitamin A supplementation and acute respiratory infection among 2-4 years old children an exploratory study of the universal approach as a nutrition policy option - Pedro, Ma. Regina A.; Bongga, Demetria C. (2001)
Universal high-dose vitamin A supplementation (VAS) aims to significantly curb child mortality in the country. Available evidence however is equivocal with regard to the impact of intervention on acute respiratory infections (ARI), a leading cause of child deaths. Adverse effects have been shown when the intervention is administered to children who may not be nutritionally deficient. It is important to ascertain if adverse effects occur in children who receive the high-dose vitamin A intervention, and which, between universal and a targeted distribution of vitamin A supplements, is more efficient in reducing respiratory morbidity, as well as mortality as a consequence. The study examined the effect of high-dose VAS on the incidence and duration of ARI among 2-4 yr old children who may not likely be nutritionally deficient. The interaction of receipt of high-dose vitamin A supplements and nutritional status, and other potential risk factors, and the effect of these interactions on ARI were investigated. The economic benefits or the efficiency of universal high-dose VAS and targeting the intervention only to at-risk children were compared. The study involved 113 2-4 yr old children with long-standing normal and mild-to-severely inadequate nutritional status, 74 of whom received a high-dose vitamin A supplement and 39 who did not, and 18 weeks of observation was carried out. ARI episodes were monitored from daily maternal records and bi-weekly home visits. Relative risk to, and odds ratio having ≥2 episodes of, ARI and increased period of illness were determined from crosstab or logistic regression. Attributable risks to being ill with ARI due to vitamin A supplementation were determined. The effect of the intervention was translated into economic terms, using human capital valuation, and compared with costs of carrying out the program to estimate benefit cost. Two approaches for VAS were compared: a universal vs. targeted distribution of the high-dose vitamin A based on risk criterion identified in the study. In a community that provides preventive health care, and registers high rates of immunization and health services utilization among the children, children with acceptable vitamin A status and who consume adequate amounts of vitamin A-rich foods respond to the intervention with increased ARI risk. Vitamin A supplementation independently and in interaction with increased intake of Vitamin A-rich foods appears to increase the odds of having ≥2 episodes of ARI (β=0.832 and 0.878, respectively, p≤0.10). However, high-dose VAS protects children with inadequate consumption of vitamin A-rich foods against ARI (RR: 0.67; 95% CI: 0.48-0.92) and ARI accompanied with a combination of fever, refusal to eat or vomiting (RR: 0.78; 95% CI: 0.61-0.98). The targeted approach, focusing on children who consume inadequate vitamin A-rich foods, results to increased positive health outcomes and greater net benefits. A shift from a universal to a targeted vitamin A supplementation program will likely push government's efforts to curb child morbidity and mortality as well as ensure general well-being of the population to more significant levels.
Thesis (Ph. D. Nutrition)--University of the Philippines, Diliman.
Keywords: Vitamin A deficiency in children -- Philippines; Vitamin A -- Therapeutic use -- Effectiveness; Respiratory infections in children -- Philippines; Nutrition policy -- Philippines